Extensive sampling and high-throughput sequencing reveal Posidoniomycesatricolor gen. et sp. nov. (Aigialaceae, Pleosporales) as the dominant root mycobiont of the dominant Mediterranean seagrass Posidoniaoceanica - Vohník, Martin; Borovec, Ondřej; Kolaříková, Zuzana; Sudová, Radka; Réblová, Martina (MycoKeys, 2019)
Seagrasses provide invaluable ecosystem services yet very little is known about their root mycobiont diversity and distribution. Here we focused on the dominant Mediterranean seagrass Posidoniaoceanica and assessed its root mycobiome at 32 localities covering most of the ecoregions in the NW Mediterranean Sea using light and scanning electron microscopy and tag-encoded 454-pyrosequencing. Microscopy revealed that the recently discovered dark septate endophytic association specific for P.oceanica is present at all localities and pyrosequencing confirmed that the P.oceanica root mycobiome is dominated by a single undescribed pleosporalean fungus, hitherto unknown from other hosts and ecosystems. Its numerous slow-growing isolates were obtained from surface-sterilised root segments at one locality and after prolonged cultivation, several of them produced viable sterile mycelium. To infer their phylogenetic relationships we sequenced and analysed the large (LSU) and small (SSU) subunit nrDNA, the ITS nrDNA and the DNA-directed RNA polymerase II (RPB2). The fungus represents an independent marine biotrophic lineage in the Aigialaceae (Pleosporales) and is introduced here as Posidoniomycesatricolor gen. et sp. nov. Its closest relatives are typically plant-associated saprobes from marine, terrestrial and freshwater habitats in Southeast Asia and Central America. This study expands our knowledge and diversity of the Aigialaceae, adds a new symbiotic lifestyle to this family and provides a formal name for the dominant root mycobiont of the dominant Mediterranean seagrass.
Keywords: seagrasses; Dothideomycetes; dark septate endophytes; root endophytes; marine fungi